2021
DOI: 10.1371/journal.pone.0247735
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib exhibits therapeutic potential in experimental model of hyperlipidaemia

Abstract: Hyperlipidaemia is a major risk factor for cardiovascular diseases, the leading cause of death globally. Celecoxib attenuated hypercholesterolaemia associated with CCl4-induced hepatic injury in rats without improving liver function in our previous study. This present study investigated the lipid lowering potential of celecoxib in normal rats fed with coconut oil subjected to five deep-frying episodes. Male Sprague Dawley rats were randomly assigned to groups (n = 6 rats/group) which received physiological sal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Substantial research is being conducted to evaluate the therapeutic potential of celecoxib to target other diseases, including its effects on tendon healing. [ 11–16 ] However, contrasting results on the effect of celecoxib on tendon regeneration have been reported. Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial research is being conducted to evaluate the therapeutic potential of celecoxib to target other diseases, including its effects on tendon healing. [ 11–16 ] However, contrasting results on the effect of celecoxib on tendon regeneration have been reported. Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial research is being conducted to evaluate the therapeutic potential of celecoxib to target other diseases, including its effects on tendon healing. [11][12][13][14][15][16] However, contrasting results on the effect of celecoxib on tendon regeneration have been reported. Zhang et al [15] found celecoxib to exhibit negative effects on tenocyte differentiation and proliferation in mouse Achilles tendon injuries.…”
Section: Introductionmentioning
confidence: 99%